Relationship between psychosocial and consumption patterns among high school adolescents in the national capital city buffer area - Rahayu, Agustin Putri; Rohmah, Nur; Nurrachmawati, Annisa; Permana, Lies; Agustini, Rina Tri; Fikri, Mohammad; Feriyanti, Alma (JOURNAL OF Mental Health Concerns, 2025)
Background: Inappropriate consumption patterns among adolescents increase chronic disease risk later in life, potentially influenced by psychosocial factors. This study analyzed relationships between psychosocial factors and consumption patterns among high school students in the NCC buffer area. Purpose: To examine the relationship between psychosocial and consumption in high school adolescents in NCC buffer area Method: Using a cross-sectional design, 386 high school students were selected through proportional random sampling. Data collection employed the Kessler questionnaire for psychological distress, and questionnaires measuring family and peer support, family mental health influence, school support, and consumption patterns. Chi-square tests analyzed bivariate relationships with significance at p < 0.05. Results: Results showed no significant relationships between consumption patterns and psychological distress (p = 0.798), family and peer support (p = 0.887), family mental health influence (p = 0.951), or school support (p = 0.301). Conclusion: The study concluded that psychosocial factors do not significantly impact consumption patterns among high school adolescents in the NCC buffer area. Despite non-significant findings, this research provides important baseline data on adolescent consumption patterns in this strategic buffer area and suggests investigating other factors that may influence consumption behavior in this population.   Keyword: Adolescents; Consumption Patterns; Family Mental Health; Psychological Distres; Social Support.